The role of the self-concept in a system of guidance at the level of initial adolescence - Hall, Deryck John (Rhodes University, Faculty of Education, Department of Education, 1987)
Part One I A Perspective on Guidance II Concepts of Self This section is a review and discussion of the two conceptualizations which are fundamental to the research structure: guidance as an overall framework within which procedures are devised for the development of this understanding of the "self" . Part Two "¢ III Didactic Discovery IV The Class Citation Award A way of thinking about an ~ducational approach which could generate a classroom mileu, where the in a practical ongoing process to encourage participation and CCA is the key~ote strategy involve the group in "self" and "other" awareness. Part Three V VI Experiment, Survey, Action Research Results, Reflections and Recommendations The three research methods employed to gather evidence of pupil awareness and its implications, with a discussion patterns of self~knowledge, and its effect on the NOTE: Constant reference to thi s page, and to page xxxii will enable the reader to view the thesis as a whole
Keywords: Self-perception in adolescence; Educational counseling